Investigation of the Frequency, Causes and Consequences of Cholestasis in Infants Referred to AmirKola Children\'s Hospital During the Years 2012-2022 - Zahra Ghanbari tilami; Sanaz Mehrabani; Mohammadreza Esmaeili Dooki; Maryam Nikpour; Yadollah Zahedpasha; Mousa Ahmadpour; Abbas Hadipour (Journal of Mazandaran University of Medical Sciences)
Background and purpose: Children with cholestasis experience a wide spectrum of disease, ranging from transient liver function abnormalities to life-threatening conditions. These children may require hospitalization or specialized care at various times due to liver enzyme disorders and associated clinical issues. In severe cases, liver damage can lead to acute liver failure, necessitating liver transplantation or resulting in death. Early diagnosis of the etiology of cholestasis can be crucial for improving prognosis. This study aimed to determine the frequency, causes, and outcomes of cholestasis in infants referred to Amir Kola Children's Hospital. Materials and methods: This retrospective descriptive study included all infants with cholestasis admitted to AmirKola Children's Hospital between 2012 and 2022. Inclusion criteria were infants under 2 years of age diagnosed with cholestasis. Infants with incomplete medical records were excluded from the study. Hepatic cholestasis was diagnosed based on the infant's medical history and confirmed by a pediatric gastroenterologist. All infants underwent diagnostic evaluation tests and abdominal ultrasound. Liver biopsy was performed when necessary to assess liver pathology. Short-term outcomes of hepatic cholestasis, including length of hospitalization, frequency of hospitalization, need for special care, liver transplantation, and mortality, were evaluated. Demographic information, along with the causes and outcomes of cholestasis, were reported using measures of central tendency (mean) and dispersion (standard deviation), or as frequencies and percentages. Results: During the study period (2012-2022), 3,650 infants under 2 years of age were admitted to Amir Kola Children's Hospital. The frequency of cholestasis among hospitalized children was 54 (1.47%). The most common symptom of cholestasis was hepatomegaly, observed in 35 (64%) infants. The leading causes of cholestasis included biliary atresia in 21 (38.8%) infants, idiopathic hepatitis in 17 (31.4%) infants, and congenital metabolic disorders in 7 (12.96%) infants. Of the children in the study, 23 (42%) were hospitalized at least once, and 10 (18.5%) were hospitalized twice. Liver biopsy was performed in 32 (60.4%) of the 54 children; 11 had neonatal cholestasis, 7 had normal ultrasound results, and 13 had giant cell hepatitis and neonatal hepatitis (10 with normal ultrasound results), with 2 showing normal pathology reports. Additionally, 20 (37%) of these children died, 24 (44%) recovered, and 9 required liver transplantation. Conclusion: According to the results of this study, more than one-third of children with cholestasis died, with biliary atresia and idiopathic hepatitis identified as the most common causes. Biliary atresia was also the most frequent indication for liver transplantation. These findings highlight the need for timely diagnostic examinations, testing, and specialized evaluations to support early diagnosis and treatment in infancy.